Inhibition of Microbiota-dependent Trimethylamine N-Oxide Production Ameliorates High Salt Diet-Induced Sympathetic Excitation and Hypertension in Rats by Attenuating Central Neuroinflammation and Oxidative Stress - Liu, Gang; Cheng, Jiayin; Zhang, Tianhao; Shao, Yingxin; Chen, Xiangxu; Han, Lihong; Zhou, Ru; Wu, Bin (Frontiers in Pharmacology, 2022)
Excessive dietary salt intake induces neuroinflammation and oxidative stress in the brain, which lead to sympathetic excitation, contributing to hypertension. However, the underlying mechanisms remain elusive. Accumulating evidence reveals that trimethylamine-N-oxide (TMAO), a gut microbiota-derived metabolite, is implicated in the pathogenesis of multiple cardiovascular diseases. The present study sought to determine whether central TMAO is elevated and associated with neuroinflammation and oxidative stress in the brain after long-term high salt (HS) diet intake and, if so, whether inhibition of TMAO generation ameliorates HS-induced sympathetic excitation and hypertension. Sprague–Dawley rats were fed either a HS diet or a normal salt (NS) diet and simultaneously treated with vehicle (VEH) or 1.0% 3,3-Dimethyl-1-butanol (DMB, an inhibitor of trimethylamine formation) for 8 weeks. HS+VEH rats, compared with NS+VEH rats, had elevated TMAO in plasma and cerebrospinal fluid (CSF), increased blood pressure (BP), and increased sympathetic drive as indicated by the BP response to ganglionic blockade and plasma norepinephrine levels. HS-induced these changes were attenuated by DMB, which significantly reduced TMAO in plasma and CSF. Neuroinflammation as assessed by proinflammatory cytokine expression and NF-κB activity and microglial activity, and oxidative stress as measured by NAD(P)H oxidase subunit expression and NAD(P)H activity and ROS production in the hypothalamic paraventricular nucleus (PVN) were increased in HS+VEH rats but were decreased by DMB. DMB had no effects on above measured parameters in NS rats. The results suggest that long-term HS diet intake causes elevation in TMAO in the circulation and brain, which is associated with increased neuroinflammation and oxidative stress in the PVN, an important cardiovascular regulatory center. Inhibition of TMAO generation ameliorates HS-induced sympathetic excitation and hypertension by reducing neuroinflammation and oxidative stress in the PVN.